Back Chip Temperature in Environmentally Conscious Turning with Conventional and Internally Cooled Cutting Tools - S. A., Che Ghani; Kai, Cheng; Timothy, Minton (Faculty Mechanical Engineering, UMP, 2013)
Central to machining processes is the interaction between the tool insert and the chip of material removed from the blank. Chip-insert interaction occurs when the chip slides on the rake face of the insert. Heat is generated by the friction inherent to this sliding process. The temperature in the cutting zone of both the insert and the chip rises, usually facilitating adhesion, diffusion, and more complex chemical and physical phenomena between the insert and the chip. These effects accelerate the insert wear, ultimately undermining the tool life. Thus, a number of methods have been developed to control heat generation. Most typically, metal working fluids are conveyed onto the rake face in the cutting zone. However, this solution may be not ideal from the point of view of cost, the environment, and contamination of the part, which may be unacceptable, for example, in healthcare and optical applications. In this study, microfluidic structures internal to the insert are examined as a means of controlling the heat generation.Conventional and internallycooled tools were compared in dry turning of AA6082-T6 aluminum alloy in two 3 x 3 factorial experiments of different machining conditions. Statistical analyses support the conclusion that chip temperature depends only on the depth of cut,and not on the feed rate or cutting speed. They also show that the benefit of cooling the insert internally increases as the depth of cut increases. Therefore, internallycooled tools can be particularly advantageous in roughing operations.